A proposed biomass char classification system. (15th November 2018) - Lester, Edward; Avila, Claudio; Pang, Cheng Heng; Williams, Orla; Perkins, Joseph; Gaddipatti, Sanyasi; Tucker, Gregory; Barraza, Juan Manuel; Trujillo-Uribe, María Patricia; Wu, Tao
Graphical abstract: A sunflower particle showing how the internal structuring present in the original particle can influence the morphology of the char particles post pyrolysis. Highlights: A new biochar morphological classification system relevant to biomass researchers. The differences between biomass and coal chars are discussed clearly. A wide range of different biomass types used in industry for energy generation are considered. The link between biomass composition with char morphology is established. Abstract: A new classification system is proposed for the morphological characterisation of char structures from biomass. These char structures are unlike the coal chars that have an established nomenclature via the International Committee of Coal and Organic Petrology (ICCP) which divides char structures into thin walled and thick walled spheres and networks, mixed dense and mixed porous, fusinoids and solids. The chars from biomass show a tendency, depending on heating regime, to produce different types of internal pore structure (cellular and porous) and aspect ratio (high and low) compared with coal chars. For this reason a new classification system has been developed to cover these new structures which should assist in combustion, co-firing and gasification research where these intermediate char structures play an important role in conversion efficiency. Low heating rates (using a muffle furnace at 1000 °C and 3 min) were used to create chars from 9 different biomass types, with a range of lignocellulosic compositions. Char type appeared to depend on the biomass type itself and original lignocellulosic composition (cellulose, lignin and hemicellulose content) and cell structure.